P265 Pharmacokinetic and pharmacodynamic evaluation of radiological healing in Crohn's disease patients treated with Infliximab: a TAILORIX MRE substudy. (25th January 2019) - Bossuyt, P; Dreesen, E; Rimola, J; Devuysere, S; De Bruecker, Y; Vanslembrouck, R; Laurent, V; Zappa, M; Savoye-Collet, C; Gils, A; Vermeire, S; Peyrin-Biroulet, L
Abstract: Background: Higher infliximab (IFX) trough levels (TL) are associated with clinical and endoscopic remission in Crohn's disease (CD). The relationship between pharmacokinetic (PK) and pharmacodynamic (PD) monitoring and radiological healing evaluated by magnetic resonance enterography (MRE) are unknown. We here assessed the correlation between IFX TL and radiologic remission in a post hoc analysis of the prospective randomised TAILORIX trial. 1 Methods: This study included all patients from TAILORIX that had baseline and Week 54 MRE available. The MARIA score was calculated by two independent blinded central readers (CR). In case of discrepancy a third CR provided adjudication. Radiologic response and remission were defined as MARIA in all segments <11 and <7, respectively. Prospectively collected PK markers (IFX TL), PD markers (CRP and Faecal Calprotectin [FC]) and endoscopic remission (CD endoscopic index of severity, CDEIS <3) were used for the analysis. Results: Thirty-six patients were included in the analysis (50% female; median age 35.7 years IQR 25.6–48.6; median disease duration 1.44 months IQR 0.6–22.4). Radiologic response and remission at w54 was 32.3% and 25.8%, respectively; endoscopic remission was 67.7%. The correlation between CDEIS and MARIA at w0 was moderate (Pearson 0.46; p = 0.008), but was absent at w54. No correlation could be found between endoscopic and radiologic remission. Radiological remission at w54 was correlated with IFX TL at Week 14 ( p = 0.049) with a ROC based IFX TL cut-off value of 7.8 µg/ml (AUC 0.74 sens 75% and spec 86%; NPV 90% and PPV 67%). Radiologic response at w54 was correlated with IFX TL at w14 ( p = 0.048) with a ROC based IFX TL cut-off value of 7.8 µg/ml (AUC 0.73 sens 75% and spec 90%; NPV 87% and PPV 78%) and with continuous pharmacological response (IFX TL >5.0 µg/ml at all time points) ( p = 0.034). No difference was found in IFX TL comparing patients with or without radiologic remission or response at W54. A subgroup of 21 patients needed dose escalation. In this subgroup continuous pharmacological response (IFX >7 µg/ml at all time points) was associated with radiological response ( p = 0.042) and remission ( p = 0.010). CRP and FC were not associated with radiological remission or response at any given time point. Conclusions: In this post hoc analysis of TAILORIX, radiologic response and remission following infliximab induction and maintenance were observed in 32 and 26% of patients. IFX TL >7.8 µg/ml at the end of induction therapy predicted both radiologic remission and response at w54 in patients with CD. 1 Reference 1. D'Haens G, Vermeire S, Lambrecht G, et al . Increasing infliximab dose based on symptoms, biomarkers, and serum drug concentrations does not increase clinical, endoscopic, and corticosteroid-free remission in patients with active luminal Crohn's disease. Gastroenterology 2018;154:1343–1351.e1.